HUBUNGAN KAUSALITAS NILAI TUKAR, SUKU BUNGA DAN INDEKS HARGA SAHAM DI INDONESIA - Rosnawintang Rosnawintang (Universitas Halu Oleo, 2017)
This study aims to determine the relationship between exchange rates, SBI interest rates and the stock price index in Indonesia period January 2006- October 2010. The type of data used in this study is secondary data. The analysis tool used is Granger causality analysis with the Vector Auto Regression (VAR) method using the help of Eviews 6.0 program. The results showed that there was a two-way causality relationship between SBI interest rates and IHSG, there was a one-way causality relationship between the IHSG and the exchange rate where the JCI had a significant effect on exchange rates and there was a one-way causality relationship between the exchange rate and SBI interest rates exchange that has a significant effect on SBI interest rates.